A rare case of melanoma recti after colorectal surgery in hemorrhoid nodule: Case report of melanoma recti - Selaković, Vladimir; Ranisavljević, Milan; Vasiljević, Tijana; Stoiljković, Bratislav; Kukić, Biljana (Medicinski časopis, 2021)
Intorduction: Anorectal melanoma (AM) is an aggressive and very rare malignancy. Aim of this case report was to present a case of anorectal melanoma that occurs in hemorrhoidal node after colorectal surgery. Case report: Patient M.K. aged 69 years was treated at Oncology Institute of Vojvodina for histopathological (HP) verified melanoma of the anorectum (S100, HMB45 and Melan A positive) localized in hemorrhoidal node. Wide local excision was made. Three months after the operation secondary deposits were ocurred at the site of colorectal anasthomosis, stomach, lung and brain. Polymerase chain reaction analysis of tumor DNA found no mutation in the BRAF V600 gene. Five months after the operation patient is still alive and on supportive and symptomatic therapy. Conclusion: Despite its rarity, AM should always be considered in unusual anorectal lesions first at all in hemorrhoid nodules.